The teaching of Paul in terms of the present day the Deems lectures in New York University - Ramsay, William Mitchell, Sir, 1851-1939; Deems Lectures, New York University, November, 1910. (London, UK Hodder and Stoughton, 1913)
Includes bibliographical references.
Donated by the late Thomas Denton.
Keywords: Bible. N.T. Epistles of Paul -- Commentaries